Development, tryout and evaluation of activities for high school biology using Centrosema Pubescens - Baliton, Norma Bernal 1940- (1979)
This study aimed to determine the basic characteristics, habitat, and protein content of the leaves of the Centrosema pubescens and to develop activities which will make high school biology students understand fully the Centrosema pubescens. To insure adequacy and practicability of the activities, a tryout involving twenty-five (25) second year high schools students was conducted. To determine the appropriateness of the activities, an 8-item evaluation sheet was given to each student. The study concluded that the activities may be included as supplementary materials in the lessons on plants. Teachers can use the procedures illustrated to devise new activities.